Finance With Control System Internal as Moderation Variables Effect of Fiscal Decentralization, TransparencyAnd Performance on Report Accountability - Anasusia (JEKAMI Journal of Accounting, 2022)
This study aims to determine the effect of fiscal decentralization, transparency and performance on the accountability of financial statements with an internal control system as a moderating variable. This research was conducted at the Regional Financial and Asset Management Revenue Service. This research uses an associative-quantitative approach. Sampling with 47 respondents. In analyzing the data using multiple linear regression analysis and moderated regression analysis (MRA) with an analytic approach. The research results of multiple linear regression analysis show that fiscal decentralization does not have a positive effect on accountability of financial statements, while transparency and performance have a positive effect on accountability of financial statements. Modersion regression analysis shows that the internal control system is a moderating variable between fiscal decentralization, transparency, and performance on accountability of financial statements.